New evidence for the therapeutic potential of curcumin to treat nonalcoholic fatty liver disease in humans - Inzaugarat, María Eugenia (2017)
Fil: Inzaugarat, María Eugenia. Consejo Nacional de Investigaciones Científicas y Técnicas. Instituto de Inmunología, Genética y Metabolismo; Argentina